Analysis of Marrubiin in Marrubium alysson L. Extract Using Advanced HPTLC: Chemical Profiling, Acetylcholinesterase Inhibitory Activity, and Molecular Docking - Nermeen A. Eltahawy; Asmaa I. Ali; Salma A. Ibrahim; Mohamed S. Nafie; Amal M. Sindi; Hanaa Alkharobi; Ahmad J. Almalki; Jihan M. Badr; Sameh S. Elhady; Reda F. A. Abdelhameed (Metabolites, 2023)
The main purpose of this work is to investigate the phytochemical composition of Marrubium alysson L. non-polar fraction. GC/MS analysis was used to evaluate the plant extract’s saponifiable and unsaponifiable matter. Although M. alysson L. lipoidal matter saponification produced 30.3% of fatty acid methyl esters and 69.7% of unsaponifiable matter. Phytol was the most dominant substance in the unsaponifiable materials. Notably, marrubiin which is one of the most prominent metabolites of Marrubium alysson L. was not detected through our adopted GC/MS technique. Thus, further characterization was proceeded through simple and rapid HPTLC analysis which successfully managed to identify marrubiin. Based on the regression equation, the concentration of marrubiin in M. alysson L. extract was 14.09 mg/g of dry extract. Concerning acetylcholinesterase inhibitory activity, both the crude M. alysson L. total methanolic extract and the non-polar fraction displayed reasonable inhibitory activity against acetylcholinesterase (AChE), whereas the pure compound marrubiin was considered to be the most effective and potent AChE inhibitor, with an IC50 value of 52.66 (µM). According to the molecular docking studies, potential sites of interaction between the pure chemical marrubiin and AChE were examined. The results show that Tyr124 on AChE residue was critical to the activity of the aforementioned drug. Based on the depicted marrubin AChE inhibition activity and reported safety profile, this chemical metabolite is considered as a promising lead compound for further pre-clinical investigation as well as drug development and optimization.